ANALISIS KURIKULUM 2013 DITINJAU DARI ASPEK NILAI KARAKTER BANGSA - Muhtar, Tatang (Mimbar Sekolah Dasar, 2014)
National education is still experiencing difficulties in producing quality graduates, skilled, and creative that can serve as a driving source in various fields of development. And outputs the result of education is often a burden on the government to meet their needs for social services, employment, subsidies, and the like. They pass and emerge as new citizens who are not able to offer a solution, but rather a source of trouble and anxiety community. One source of problems in education is still weak education that can cultivate the essential values of humanity. Where today there has been a separation between "intellectual education" with "educational value". This dichotomy shows the smallness of the mind, because the moral value is not different from the intellectual dimension, but is the foundation for intellectual growth. It is necessary for the implementation of a curriculum that is based on the improvement of the competence-based character education aside from it in the process of implementation should be in accordance with how to implement character education. In this case the assessed curriculum is the curriculum in 2013. Keywords: character education, curriculum 2013, educational value.